Vademecum der Grabung Kamid-el-Loz (1969)
unter Mitarbeit von K. Emre, U. Finkbeiner, W. Gebers, G. Gerlach, M. Hein, G. Krause, Fr. Much, R. Poppa, J. Reichstein, H.-P. Schäfer, M. Wilbertz; Saarbrücker Beiträge zur Altertumskunde (hrsg. von R. Hachmann und W. Schmitthenner); ersch. 1971.